STRATEGI PEMBELAJARAN BAHASA ARAB PADA MAHASISWA PENDIDIKAN ISLAM ANAK USIA DINI SEMESTER I INSTITUT KH. ABDUL CHALIM - Muhammad Reza Fahlefi; Ummah, Nahdiyatul (Institut Kariman Wirayudha Sumenep, 2024)
Abstract This study aims to analyze Arabic learning strategies used in the department of early childhood Islamic education, semester I, KH. Abdul Chalim Institute. Qualitative research methods were applied to describe behaviors, events, and learning contexts in detail. Data were collected through in-depth interviews, observation, and documentation, with the main informants consisting of lecturers and students. The results showed that strategies such as the expository method, sam`iyah wasyafawiyah, and mubasyaroh were effective in improving students' speaking and reading skills. Supporting factors include the availability of relevant teaching materials and the strong religious background of the students. Conversely, barriers identified include students' lack of confidence in speaking Arabic and limited resources. The findings underscore the importance of planning and implementing structured and contextualized learning strategies. This study makes an important contribution to the development of Arabic language learning strategies in Islamic educational settings, as well as a reference for further research in this field. Hopefully, the results of this study can assist educational institutions in improving the quality of Arabic language teaching, preparing students to face academic challenges with more confidence, and achieving optimal learning objectives. Keywords: Learning strategies, Arabic language, early childhood education, qualitative methods.